STATUS KAUM SAYYID DALAM PRANATA SOSIAL ADAT MASYARAKAT CIKOANG KABUPATEN TAKALAR - Fitriani, Fitriani; Risal, M. Chaerul; Yeyeng, Andi Tenri (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2023)
The title Sayyid which is reserved for the descendants of the Prophet in the social strata cannot be separated from the public spotlight. Sayyid's position in terms of religion and education outlines relationships and inclusive movements in society. This study aims to determine the status of the Sayyid in the customary social order of the Cikoang Community. The type of research used is qualitative research. The results of the study show that the Sayyid group in the Cikoang community has strong social institutions that have an impact on the highest social status in society. The religious understanding and wisdom of the Sayyid group encourages special recognition and degree in the reality of the community's traditional institutions, including those in marriage ties and celebratory traditions. Meanwhile, Islamic teachings emphasize that human equality is not measured in the social strata that accompany it, but in piety and faith.